PENERAPAN MODEL INKUIRI TERBIMBING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA TEMA 2 BAB 1 PEMBELAJARAN 2 KELAS V UPTD SD INPRES OESAPA KECIL 1 KUPANG - Koroh, Taty R.; Adoe, Treesly Y.N.; Silla, Deti Demercy (Universitas Nusa Cendana, 2024)
The aim of this study is to explain the application of the guided inquiry model to improve student learning outcomes in human respiratory system material for fifth grade students at SD Inpres Oesapa Kecil 1 Kupang. Data is collected through observation, tests and documentation. The research subjects consisted of 23 fifth grade students at SD Inpres Oesapa Kecil 1 Kupang, consisting of 9 female students and 14 male students. The data in this research was analyzed qualitatively and quantitatively. The findings from this research show that 20 out of 23 students achieved the criteria for achieving learning objectives very well, while 3 students did not reach the criteria for achieving learning objectives. From the results of the assessment percentage, it can be concluded that 83.04% of students have achieved or exceeded the minimum standards determined by the school, namely 75%.